PTH-013 Missed Opportunities for Colorectal Cancer Diagnosis and Impact on Medium-Term Survival. (4th June 2013) - Vaughan-Shaw, P G; Knight, H; Aung, M; Williams, T; Borley, N R; Wheeler, J M
Abstract : Introduction: Delays to diagnosis of colorectal cancer (CRC) may impact upon patient outcome. There is an accepted false-negative rate for all endoscopic or radiological investigations, yet clinicians may be falsely reassured by negative findings. This study identifies cases of CRC diagnosed late after negative investigations and determines outcome in this cohort. Methods: A retrospective comparative cohort study was performed. Cases of CRC over a 12-month period were identified. Radiological and endoscopic investigations performed up to 5 years previously were reviewed. Episodes of negative investigations were considered 'missed' opportunities for diagnosis. Clinical outcomes were compared using chi-squared test and Kaplan-Meier survival curves. Results: 396 colorectal cancers were identified with 214 (54%) males and median age 72. Of these, 29 (7%) patients had undergone negative investigations including colonoscopy (n = 8), flexible sigmoidoscopy (n = 7), barium enema (n = 7) and CT for abdominal symptoms (n = 20) ('missed' group) within the previous 5 years, median 817 days prior to diagnosis. Age, mode of presentation, tumour site, pT and pN stage were comparable between groups. Metastases at presentation were more common in the 'missed' group (28% vs. 14%, p = 0.046) and survival at median follow-up of 416 days was significantly reduced (66% vs. 88%, p = 0.0004). Conclusion: A small proportion (7%) of patients with colorectal cancer has undergone previous negative abdominal or colonic investigation. Such episodes may represent missed opportunities for diagnosis and survival is significantly reduced in such patients. The recognition that endoscopic and radiological investigations may miss lesions should encourage repeat or alternative interval investigations where concerning symptoms exist. Disclosure of Interest: None Declared.